Measurement and Evaluation Method of Distributed Optical Fiber Acoustic Sensing Performance - Zhiyuan Xie; Yuwei Sun; Anqiang Lv; Qian Xu (Photonics, 2024)
Distributed acoustic sensing incorporates multiple indicators, and there exists a mutually constraining relationship among these indicators. Different application fields have varying requirements for indicators. Therefore, indicator testing and comprehensive evaluations are crucial for engineering applications. In this paper, we conducted a theoretical analysis of key indicators, including frequency response, sensitivity, spatial resolution, sensing distance, multi-point perturbation, and temperature influence. The indicator test scheme was developed, and a test system was constructed. The test data were analyzed and compared in the time-frequency domain. A performance evaluation method for distributed acoustic sensing, based on the analytic hierarchy process, is proposed, and a comprehensive evaluation example focused on high-frequency applications is presented. The results show that the test scheme and method presented in this paper can accurately measure the upper limits of each indicator of distributed acoustic sensing. The proposed comprehensive evaluation method enables the assessment of sensor performance and applicability based on engineering practices. It addresses the challenge of evaluating distributed acoustic sensing with multiple indicators and offers an efficient approach for equipment development and engineering applications.